Rezension von: Leidorf, Klaus; Ettel, Peter; Irlinger, Walter; Zeune, Joachim, Burgen in Bayern - Schulze, Ute (Württembergisch Franken, 2001)
Klaus Leidorf, Peter Ettel, Walter Irlinger, Joachim Zeune, Burgen in Bayern. 7000 Jahre Geschichte im Luftbild. Mit Beiträgen von Björn-Uwe Abels , Jochen Haberstroh, Dieter Neubauer, Michael M. Rind, Karl-Heinz Röhrig, Stuttgart (Theiss) 1999. 208 S., ca. 300 farbige Abb., ca. 80 Pläne